Analysis of approaches and tools for regulating the asymmetry of territory development - O. A. Mukhoryanova; I. S. Gruzinova; E. S. Budagyan (Вестник Северо-Кавказского федерального университета)
Introduction. The conditions for the development of the country that have emerged in recent years have led to increased intraregional differentiation, which has negatively affected the efficiency of the territorial economy and the social well-being of the population.Goal. As the goal of the study, we identified the consideration of various approaches and tools for regulating the asymmetry of territory development, used at the present stage of regional development, with the subsequent development of optimal solutions in the field of its socio-economic development.Materials and methods. Within the framework of the study, in order to analyze individual approaches and tools, general scientific and specific scientific research methods, methods of logical-methodological, structural-functional and system analysis were used. Such methods of scientific knowledge as causal modeling, induction and deduction, multifactor analysis and synthesis, analogy, and system-situational approach were also used.Results and discussion. In the course of the work, it was discovered that at the moment there is no single developed, tested and proven effective method for smoothing intra-regional asymmetry, and existing methods have serious shortcomings that do not allow taking into account the territorial characteristics of the region. Having carried out their comparative analysis, we chose the optimal method the intraregional differentiation of municipalities, which allows us to group them according to key characteristics and examine the level of deviations in each group.Conclusion. Based on the results of the study, we can conclude that the formation of an effective policy for intraregional territorial alignment of asymmetry is possible by stimulating the development of “growth points” both within a specific territory and in integration with surrounding territories. At the same time, comprehensive work should be carried out in parallel to develop municipalities that lag behind in the main parameters of socio-economic development.